Sustainable Mineral Development: Possibilities and Pitfalls illustrated by the Rise and Fall of Dutch Mineral Planning Guidance - M. J. van der Meulen (Society for Mining, Metallurgy & Exploration, 2005)
"The Netherlands has major resources of sand, gravel and clay, exploited mainly for construction works and the building materials industry. As in most western countries, mineral extraction meets with considerable societal resistance. To this end, Dutch minerals policy aims to prevent extraction by promoting economical use of materials, and the use of alternative (secondary or renewable) materials. Up till recently, it also included a system of production planning to sustain supplies of regionally scarce materials. Dutch policy development is reviewed and discussed in terms of pitfalls and possibilities for mineral planning in general. Promoting secondary substitution has been quite successful, and presents an example. In contrast, the production planning system has been controversial from the start and ineffective as a result, mainly because it attempted to solve supply problems without properly addressing the underlying resistance. For this reason the system is in the process of being abandoned. The full paper will be published in: Petterson, M., McEvoy F, & Marker, B.R. (Eds) 2005, Sustainable minerals operations in the developing world, Geol. Soc. Lond. Special report series, in press. This abstract is reprinted with kind permission of the publisher."